Post-Truth dan Tantangannya dalam Dunia Pendidikan - Achmad, Achmad Rifki Ibnu Maulana; Ahsan, Ahsan Ahmad Syarif (Paradigma: Jurnal Kalam dan Filsafat, 2025)
The post-truth phenomenon marks a fundamental shift in how society perceives truth, where emotions and subjective opinions overshadow objective facts. In the field of education, this condition undermines scientific authority, trust in knowledge institutions, and students’ critical thinking abilities. This article analyzes the epistemological crisis caused by post-truth through the lens of philosophy of science, drawing on the ideas of Plato, Immanuel Kant, and Karl Popper. These thinkers offer theoretical frameworks to understand and respond to disinformation: from the realm of ideal forms and absolute truth (Plato), the autonomy of reason and freedom of thought (Kant), to the spirit of critical inquiry and falsifiability (Popper). This study employs a qualitative method with a library research approach, examining classical and contemporary philosophical texts alongside secondary data on digital disinformation, the crisis of trust in science, and weak media literacy among students. The analysis reveals that post-truth is not merely an information crisis, but a deeply rooted epistemological crisis. Therefore, education must reinforce critical literacy, philosophical reflection, and a scientific mindset. Integrating philosophy of science into the curriculum is a crucial transformative strategy to strengthen the intellectual resilience of younger generations in navigating an increasingly complex and distracting post-truth era.